Mister Exam

Other calculators


(x-4)(x+4)

Sum of series (x-4)(x+4)



=

The solution

You have entered [src]
  oo                 
 __                  
 \ `                 
  )   (x - 4)*(x + 4)
 /_,                 
x = 1                
x=1(x4)(x+4)\sum_{x=1}^{\infty} \left(x - 4\right) \left(x + 4\right)
Sum((x - 4)*(x + 4), (x, 1, oo))
The radius of convergence of the power series
Given number:
(x4)(x+4)\left(x - 4\right) \left(x + 4\right)
It is a series of species
ax(cxx0)dxa_{x} \left(c x - x_{0}\right)^{d x}
- power series.
The radius of convergence of a power series can be calculated by the formula:
Rd=x0+limxaxax+1cR^{d} = \frac{x_{0} + \lim_{x \to \infty} \left|{\frac{a_{x}}{a_{x + 1}}}\right|}{c}
In this case
ax=(x4)(x+4)a_{x} = \left(x - 4\right) \left(x + 4\right)
and
x0=0x_{0} = 0
,
d=0d = 0
,
c=1c = 1
then
1=limx((x+4)x4x3x+5)1 = \lim_{x \to \infty}\left(\frac{\left(x + 4\right) \left|{\frac{x - 4}{x - 3}}\right|}{x + 5}\right)
Let's take the limit
we find
True

False
The rate of convergence of the power series
1.07.01.52.02.53.03.54.04.55.05.56.06.5-5050
Numerical answer
The series diverges
The graph
Sum of series (x-4)(x+4)

    Examples of finding the sum of a series